2024
DOI: 10.2174/1570159x21666230803101629
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin and Neurotensin Receptors in Stress-related Disorders: Pathophysiology & Novel Drug Targets

Abstract: Neurotensin (NT) is a 13-amino acid neuropeptide widely distributed in the CNS that has been involved in the pathophysiology of many neural and psychiatric disorders. There are three known neurotensin receptors (NTSRs), which mediate multiple actions, and form the neurotensinergic system in conjunction with NT. NTSR1 is the main mediator of NT, displaying effects in both the CNS and the periphery, while NTSR2 is mainly expressed in the brain and NTSR3 has a broader expression pattern. In this review, we bring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 210 publications
0
4
0
Order By: Relevance
“…Similarly, behavioral activity was preserved in spontaneous locomotor activity using the open field test. SE and related hippocampal excitotoxic lesions are known to induce hyperactivity in rats (dos Santos et al, 2000;Kubová et al, 2004) and mice (Chen et al, 2002;Müller et al, 2009) (reviewed in (Mattson, 2017), neuroinflammation, as shown by pro-inflammatory glial markers such as astrocytic GFAP or microglial Iba1, endothelial and BBB damage (Kyriatzis et al, 2024(Kyriatzis et al, , 2021. Hence, it has been shown in the different models that PIH increased BDNF and vascular endothelial growth factor (VEGF), reduced the proapoptotic caspase-3 activation, BAX, and MMP-9 expression, decreased expression of inflammatory factors including monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-1α (MIP-1α), two key chemokines in the regulation of microglia activation and infiltration.…”
Section: Vh-n412 Preserves Learning and Memory Abilities Exploratory ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, behavioral activity was preserved in spontaneous locomotor activity using the open field test. SE and related hippocampal excitotoxic lesions are known to induce hyperactivity in rats (dos Santos et al, 2000;Kubová et al, 2004) and mice (Chen et al, 2002;Müller et al, 2009) (reviewed in (Mattson, 2017), neuroinflammation, as shown by pro-inflammatory glial markers such as astrocytic GFAP or microglial Iba1, endothelial and BBB damage (Kyriatzis et al, 2024(Kyriatzis et al, , 2021. Hence, it has been shown in the different models that PIH increased BDNF and vascular endothelial growth factor (VEGF), reduced the proapoptotic caspase-3 activation, BAX, and MMP-9 expression, decreased expression of inflammatory factors including monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-1α (MIP-1α), two key chemokines in the regulation of microglia activation and infiltration.…”
Section: Vh-n412 Preserves Learning and Memory Abilities Exploratory ...mentioning
confidence: 99%
“…Modulators of the NT system may regulate neuroprotective pathways that are probably common to the different models of brain pathology evoked above. These models display neuronal excitotoxicity (reviewed in (Mattson, 2017), neuroinflammation, as shown by pro-inflammatory glial markers such as astrocytic GFAP or microglial Iba1, endothelial and BBB damage (Kyriatzis et al, 2021(Kyriatzis et al, , 2024 and IL-6 was also shown to be decreased or prevented. Meanwhile, TH treatments increased the expression of M2 type reactive anti-inflammatory factors including IL-10, Fizz1, Ym1, and arginase-1 and the expression of the anti-apoptotic Bcl-2 (Choi et al, 2012;Wei et al, 2013;Lee et al, 2014;Gu et al, 2015;Lee et al, 2016;Jiang et al, 2017;Zhao et al, 2020).…”
Section: Vh-n412 Preserves Learning and Memory Abilities Exploratory ...mentioning
confidence: 99%
“…Pharmacological approaches have revealed a role of Nts in analgesia, arousal, blood pressure, feeding, reward, sleep, the stress response and thermoregulation (12)(13)(14)(15). Recently, studies have started to unravel the role played by specific populations of neurotensinergic neurons in feeding (16,17) and drinking behaviors (18) as well as in sleep (19,20) and appetitive and reinforcing aspects of motivated behaviors (21).…”
Section: Introductionmentioning
confidence: 99%
“…provide available animal and human findings on epigenetics with respect to fear, anxiety, and stress-related states with an emphasis on histone modifications [ 6 ]. Kyriatzis et al review current findings on the involvement of the neurotensinergic system in stress response and the pathophysiology of stress-related disorders, with an emphasis on gene, mRNA, and protein alterations, behavioral and pharmacological studies and therapeutic implementations [ 7 ]. Providing insights from mass spectrometry and nuclear magnetic resonance metabolomic studies in rodent models, Papageorgiou et al investigate affected molecular pathways upon stress exposure and provide insightful information on stress-induced systemic changes in the brain and the periphery [ 8 ].…”
mentioning
confidence: 99%